Industry 4.0 + Industry 5.0 = Happy Marriage Between Humans and Technology - Beryl ter Haar (Italian Labour Law e-Journal)
In this paper it will be argued that the addition of human-centred Industry 5.0 to the technological innovation driven Industry 4.0 has the potential to lead to a happy marriage between humans and technology. After addressing the impacts of Industry 4.0 on work based on a literature review, the aim and aspirations of Industry 5.0 are assessed based on documents from the European Commission. The aspirations of Industry 5.0 are further evaluated in the wider context of paradigm shift in socio-economic thinking from a productivity and profit driven neoliberal free market economy to a human centred and planetary boundaries respecting wellbeing economy. Following the paradigm shift and new work narratives that come with it, the paper continues with a rethinking of the regulatory approach of work by introducing two new foundational principles. The paper concludes that with such new foundational principles, the aspirations of Industry 5.0 may lead to a more human friendly technology driven Industry 4.0.